UNHCR’s Origins and Early History: Agency, Influence, and Power in Global Refugee Policy - Loescher, Gil (Refuge: Canada's Journal on Refugees, 2017)
This article assesses the role and functions of UNHCR during its formative years and explores its agency, influence, and use of power in global refugee policy. During most of the Cold War, UNHCR’s first four high commissioners employed delegated authority and expertise on refugee law and protection, thereby convincing states of the Office’s usefulness to international stability and ensuring its survival, growth, and power. It concludes by arguing that the Office should use the lessons of this early period of its history to explore ways to exercise similar attributes today.